Endoplasmic reticulum stress-related prognosis signature characterizes the immune landscape and predicts the prognosis of colon adenocarcinoma - Cao, Lichao; Dai, Haoyang; Wei, Shangqing; Ba, Ying; Chen, Fang; Chen, Yingying; Yu, Chendi; Zhang, Shenrui; Chen, Erfei; Zhang, Hezi (Frontiers in Genetics, 2025)
BackgroundColon adenocarcinoma (COAD) is characterized by high mortality and poor prognosis. Endoplasmic reticulum stress-related gene (ERSG) plays an indispensable role in the progression and immunotherapy of COAD. In this study, we evaluated the prognostic value of ERSGs in COAD.MethodsWe constructed and validated the ERSG-related prognostic signature based on public databases using univariate Cox analysis, Kaplan–Meier survival analysis, the LASSO method, and multivariate Cox analysis. In addition, TCGA-COAD, the Human Protein Atlas, and quantitative real-time PCR (q-PCR) were used to detect the mRNA and protein expressions of ERSGs in normal and cancer tissues/cells. The immunotherapeutic cohort was used to evaluate the predictive value of the ERSG signature for immunotherapeutic sensitivity.ResultsThe ERSG signature, consisted of HSPA1A, SERPINA1, and DAPK1, could predict the prognosis of patients with COAD. Clinicopathologic characteristics were significantly correlated with risk scores. There were significant differences in the proportion of tumor-infiltrating immune cells, the TP53 mutation rate, the expression of immune checkpoint-related genes, and IC50 of the chemotherapeutic drugs between the low- and high-risk groups. Compared with normal tissues, the mRNA and protein expressions of three ERSGs were decreased in cancer tissues. Compared with NCM460, the mRNA levels of HSPA1A and DAPK1 were decreased in the majority of COAD cell lines, whereas the mRNA level of SERPINA1 was increased in HCT116 and SW480, and reduced in SW620. The ERSG signature could be used as a predictor of immunotherapeutic outcomes.ConclusionThe ERSG signature has a predictive value in the prognosis and immunotherapeutic sensitivity in COAD, helping guide the personalized treatment.